Optimising Global Competitiveness of MSMEs through Innovative Strategies for Digital Business Development - Sutrisno, Sutrisno; Susanti, Ike; Murthada (PT. LITERASI SAINS NUSANTARA, 2024)
In the current era of globalisation, rapid changes are taking place in the business paradigm. Digital transformation has become the main key in advancing business at the global level. Therefore, efforts to optimise the competitiveness of MSMEs are a must to remain relevant and compete in an increasingly competitive global market. This research aims to explore and identify optimal innovative strategies for MSME digital business development. This research uses a qualitative literature review method by retrieving data from Google Scholar from 2022 to 2023. The study results show that optimising the global competitiveness of Micro, Small and Medium Enterprises (MSMEs) through innovative strategies for digital business development is not just an option, but a necessity in this digital era. As the backbone of the economy, MSMEs need to utilise information technology, e-commerce, and digital platforms to create a competitive advantage in the global market. With the adoption of digital innovation, MSMEs can improve operational efficiency, expand markets, and build sustainable collaborations.